Transmission of monetary policy shocks in Finland: evidence from bank level data on loans - Jukka Topi; Jouko Vilmunen (European Central Bank (ECB), 2001)
We use a panel of quarterly time series observations on Finnish banks to estimate reduced form equations for the growth rate of bank loans. By allowing for individual bank specific effects in the empirical models we specifically seek evidence of a bank-lending channel for the transmission of monetary policy shocks in Finland. On the basis of our estimation results, we conclude that there is weak evidence in favour of the bank-lending channel for monetary policy shocks. Our data overlaps with the post crisis recovery of the Finnish banking sector with specific government support measures still active during the good part of the sample period. We try to capture the effects of these measures through a policy dummy variable in our empirical models. This policy dummy is highly significant, suggesting that the measures may have contributed to the growth rate of bank loans during the sample period
Keywords: E51; E52; G21; 330; banking crisis; credit view; GMM; monetary policy; money view